2010
DOI: 10.1017/s1366728910000106
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of conceptualization patterns in bilinguals: The construal of motion events in Turkish and German

Abstract: In the present article we provide evidence for the occurrence of transfer of conceptualization patterns in narratives of two German-Turkish bilingual groups. All bilingual participants grew up in Germany, but only one group is still resident in Germany (n = 49). The other, the returnees, moved back to Turkey after having lived in Germany for thirteen years (n = 35). The study is based on the theoretical framework for conceptual transfer outlined in Jarvis and Pavlenko (2008) and on the typology of satellite-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 45 publications
4
82
0
Order By: Relevance
“…First, our findings inform us about the role of language dominance in bilinguals. Most previous studies only found transfer from the dominant to the weaker language, suggesting a crucial role for language dominance (Argyri & Sorace, 2007;Daller et al, 2011;Montrul & Ionin, 2010;Serratrice, 2007). The bilinguals in our study were second-generation heritage speakers of Turkish.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…First, our findings inform us about the role of language dominance in bilinguals. Most previous studies only found transfer from the dominant to the weaker language, suggesting a crucial role for language dominance (Argyri & Sorace, 2007;Daller et al, 2011;Montrul & Ionin, 2010;Serratrice, 2007). The bilinguals in our study were second-generation heritage speakers of Turkish.…”
Section: Discussionsupporting
confidence: 44%
“…A less frequently posed question is to what extent the weaker, yet first language may affect the L2. Studies that looked at both directions have demonstrated transfer from the dominant language to the weaker language, but not vice versa (Argyri & Sorace, 2007, for the syntax-discourse interface; Daller, Treffers-Daller, & Furman, 2011;Hohenstein, Eisenberg, & Naigles, 2006, for conceptualisation patterns of motion events; Montrul & Ionin, 2010, for morpho-syntax). Furthermore, Serratrice (2007) found no transfer from the non-dominant language (English) in bilingual English-Italian children, regarding the use of subject pronouns.…”
Section: On-line Processingmentioning
confidence: 99%
“…In a recent study on German (S-framed)-Turkish (V-framed) bilinguals, Daller, Treffers-Daller and Furman (2011) investigated possible transfer effects between the two languages at the level of conceptual construal, i.e., in the process of building up a temporary conceptual representation of a motion event. They found that depending on the dominant language, bilingual speakers select concepts which conform with the grammatical and lexical pattern of this language in all contexts.…”
Section: The Study Of Motion Events In L2 Acquisitionmentioning
confidence: 99%
“…, gestures (Gullberg 2011), event conceptualization (Daller, Treffers-Daller, and Furman 2011;Treffers-Daller and Tidball in press, von Stutterheim et al 2012) and colour perception (Athanasopoulos 2009) reveal that L2 users differ significantly from monolinguals in how they conceptualize events, how they categorize objects and also in the gestures they make to accompany their speech. In addition, the variables that modulate such restructuring of conceptualization and cognitive patterns in bilinguals include increasing L2 proficiency, age of onset of bilingualism and length of stay in the L2-speaking country.…”
Section: Introductionmentioning
confidence: 99%